Equivalence Relations in Information Retrieval Thesaurus - Gopinath, M. A. (Journal of Information and Knowledge, 1985)
Differentiates between linguistic equivalence of terms from that of information retrieval situations. Presents a set of seven varieties of equivalence relations on the basis of the "used for" relations found in textile and energy thesauri. Some criteria for preferred terms from a set of equivalent terms are listed.